Association between cumulative grade point average and clinical performance and the factors affecting clinical performance among UITM Optometry Students / Mohamed Hazrul Alif Mohamed Kamaruddin - Mohamed Kamaruddin, Mohamed Hazrul Alif (2016)
Introduction: Clinical performance serves as one of the criteria to ensure a minimum level of competency at the end of their school year. Studies in predicting clinical competence based on Cumulative Grade Point Average (CGPA) had been inconclusive, saying to the fact that CGPA says little about a student to be successful in the real world. Thus, this study aims to determine the relationship between Optometry students CGPA and their clinical performance and the factors affecting clinical performance. Methods: Under a cross-sectional study design, a questionnaire was distributed to thirty-two (32) fourth-year optometry students and analyzed using descriptive analysis and spearman correlation. Results: It was found that the association between CGPA and clinical performance was insignificant (p>0.05). Furthermore, the factors affecting clinical performance were time management and anxiety. Conclusions: As no association was found between CGPA and clinical performance, it can be said that to excel within the clinic, it does not depend on the grade a student had accumulated during their studies. In addition to not be anxious and have good time management skills, a student should be proactive and empathetic when dealing with patients in order to provide the best care possible.